2018
DOI: 10.1002/jcp.27596
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin G1 induced TNF‐α‐dependent lung inflammation to enhance DNA damage in alveolar epithelial cells

Abstract: Aflatoxin G1 (AFG1), a member of the AF family with cytotoxic and carcinogenic properties, could cause DNA damage in alveolar type II (AT‐II) cells and induce lung adenocarcinoma. Recently, we found AFG1 could induce chronic lung inflammation associated with oxidative stress in the protumor stage. Chronic inflammation plays a critical role in cigarette smoke or benzo[a]pyrene‐induced lung tissues damage. However, it is unclear whether and how AFG1‐induced lung inflammation affects DNA damage in AT‐II cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Further, these radicals attack the cellular DNA, as evidenced by the increased levels of serum 8-OHDG (Figure 1). In addition, AFB 1 metabolites form AFB 1 -DNA adducts that induce DNA and cell damages and inhibit enzyme and protein synthesis through binding to nucleoproteins and nucleic acids [49]. Diabetes mellitus and AFB 1 intoxication-induced oxidative stress in this study were associated with increased production of proinflammatory cytokines, IL-1β, IL-6, and TNF-α ( Figure 1) leading to hepatorenal injuries and the elevation of activities and levels of their function biomarkers.…”
mentioning
confidence: 61%
“…Further, these radicals attack the cellular DNA, as evidenced by the increased levels of serum 8-OHDG (Figure 1). In addition, AFB 1 metabolites form AFB 1 -DNA adducts that induce DNA and cell damages and inhibit enzyme and protein synthesis through binding to nucleoproteins and nucleic acids [49]. Diabetes mellitus and AFB 1 intoxication-induced oxidative stress in this study were associated with increased production of proinflammatory cytokines, IL-1β, IL-6, and TNF-α ( Figure 1) leading to hepatorenal injuries and the elevation of activities and levels of their function biomarkers.…”
mentioning
confidence: 61%
“…The lung appears to be the most common target for DNA damage with 8-oxo-dG accumulating mainly in mitochondria and the nucleus [74,77,78]. A recent study demonstrated that AFG1 upregulated the expression of tumor necrosis factor (TNF)-α and CYP2A13 in mice alveolar type II (AT-II) cells of lung tissues, and in vitro in human AT-II-like cells (A549), which mediate an inflammation with increased numbers of γ-H2AXand 8-OHdG-positive cells in the inflamed tissues [79]. According to the authors, the inflammatory reaction induced by TNF-α upregulates the expression of CYP2A13, which in turn sustains active metabolism of AFG1 leading to ODD, as evidenced by the increased expression of the DNA damage marker γ-H2AX.…”
Section: Oxidative Stress-mediated Genotoxicitymentioning
confidence: 99%
“…Intermittent intake of AFB1 simulating the actual situation was also reported to result in an alternation of suppressive and stimulatory/compensatory effects upon exposure and resting (aflatoxin-free diet) periods, respectively [119]. Despite the conflicting data and lack of consensus regarding the cytokine types induced in response to aflatoxin exposure, the unnecessary upregulation of the immune response stimulates the production of tissue-damaging inflammatory molecules and free radicals leading to chronic inflammation, cancer, and nervous system degenerative diseases [21,79]. Moreover, low levels of a mixture of aflatoxins (AFB1, AFB2, AFG1, and AFG2) increased the antigen-presenting capacity of dendritic cells that stimulate T-cell proliferation, which has been suggested to breakdown the immunological tolerance and increase host susceptibility [134].…”
Section: Immunostimulationmentioning
confidence: 99%
“…The mice were euthanized and lung tissue was collected, after which total lung mononuclear cells were isolated using a previously described technique. 29,31 Fc receptors were blocked with anti-CD16/32 antibodies for 10 minutes, and the cells were then stained with antibodies against CD4 and CD25 for 30 minutes. The cells were analyzed using a flow cytometer (BD, FACS Calibur).…”
Section: Flow Cytometrymentioning
confidence: 99%